PEMBANGUNAN KESADARAN HUKUM MASYARAKAT MELALUI DESA SADAR HUKUM DI KABUPATEN LEMBOK TIMUR - Mulyani, Basri; MAKSUM, HAIRUL; Johan (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2021)
Legal counseling in the form of a Legal Awareness Village departs from the awareness of members of the community and local village government who on their own will strive to increase awareness and legal knowledge for themselves and village government officials. The purpose of developing a law-aware village is the realization of community legal awareness. Legal awareness is the output of the process of counseling and coaching activities that reach an ideal optimization level marked by a sense of respect for the law. The method used in this activity is in the form of a focused discussion that begins with counseling / lectures then continues with direct questions and answers. The extension participants were members of the community, especially women and local community leaders. By understanding the law, it is hoped that the community's legal awareness will increase to respect the law. The issue of marriage under the age of 19 was the most questionable discussion in the three locations of legal counseling, namely Padak Guar village, Gereneng village and Masbagik Utara Baru village, East Lombok district and other legal issues related to the conditions of each village.